CFD Modelling of the Thermal Performance of Fruit Packaging Boxes - Influence of Vent-Holes Design - Ilangovan, Adhiyaman (2021)
The shelf life of perishable products depends mainly on the conservation of air temperature. Packaging boxes are usually used to accommodate food products during cold storage and transport and/or display. The design of the vent-holes of the packaging box must promote cold airflow and remove the field heat of the produce after harvest at a short time. This study describes the influence of the vent-holes design and its performance during cold storage. The cooling performance of the different packaging boxes is evaluated experimentally and numerically using Computational Fluid Dynamics (CFD). Three new packaging box configurations with the same size but different vent-holes design (size, shape and position) and a reference box are modelled. The transient three-dimensional CFD model predicts the airflow pattern and temperature distribution within the different packaging boxes. The best thermal performance packaging achieved a fruit model temperature 1.5 K to 5 K lower than the other configurations at the end of 8 h of cooling. These predictions allow the development of new packaging box designs that promote the shelf-life extension of perishable products.